Advertising Stereotypes and Gender Representation in Social Networking Sites/Estereotipos publicitarios y representaciones de género en las redes sociales - Tortajada, I; Araüna, N; Martínez, I J (Comunicar)
This article presents the results of a quantitative and qualitative analysis of adolescent self-presentations in Fotolog. The images which these adolescents create and share through the Net focus on the construction of the Self. Here gender and sexuality become the main structuring factors of representation. Results point to the fact adolescents self-presentations mirror some of the categories defined by Goffman in his study of gender hyperritualization in advertising. Moreover, other gender expressions are found in the sample, such as the lesbian pose or the erotization of bodies which Gill also detects in advertising. Despite the fact that the images that adolescents upload in Social Networking Sites reproduce gender stereotypes and patriarchal patterns based in advertising, it must be said that they also elaborate a relatively varied repertoire of pictures and are able to conceive original creations. These creative self-representations are the outcome of a process of negotiation of gender and sexual identity which occurs in these settings, as well as in other adolescent media practices. To avoid a thoughtless reproduction of gender stereotypes and contribute to a critical negotiation of these representations, media education is needed. This media education should take into account the way in which adolescent practices are shaped by other media consumption. [PUBLICATION ABSTRACT]